Combination of veno-arterial extracorporeal membrane oxygenation and hypothermia for out-of-hospital cardiac arrest due to Taxus intoxication. Issue 6 (November 2014) - Thooft, Aurélie; Goubella, Ahmed; Fagnoul, David; Taccone, Fabio S.; Brimioulle, Serge; Vincent, Jean-Louis; De Backer, Daniel
Abstract: A young woman presented with cardiac arrest following ingestion of yew tree leaves of the Taxus baccata species. The toxin in yew tree leaves has negative inotropic and dromotropic effects. The patient had a cardiac rhythm that alternated between pulseless electrical activity with a prolonged QRS interval and ventricular fibrillation. When standard resuscitation therapy including digoxin immune Fab was ineffective, a combination of extracorporeal membrane oxygenation (ECMO) and hypothermia was initiated. The total duration of low flow/no flow was 82 minutes prior to the initiation of ECMO. After 36 hours of ECMO (including 12 hours of electrical asystole), the patient's electrocardiogram had normalized and the left ventricular ejection fraction was 50%. At this time, dobutamine and the ECMO were stopped. The patient had a full neurologic recovery and was discharged from the intensive care unit after 5 days and from the hospital 1 week later.